Aktivitas Antioksidan Senyawa yang berasal dari Kayu Artocarpus heterophyllus - ENOS TANGKE ARUNG; KUNIYOSHI SHIMIZU (JURNAL ILMU KEFARMASIAN INDONESIA, 2011)
Isoprenoid-substituted flavonoids were isolated from the wood of Artocarpus heterophyllus bybiologically activity-guided fractionation, namely antioxidant. The isolated compounds are cudraflavoneC, kuwanon C, norartocarpin, albanin A and artocarpanone have more hydroxyl groups seem to bespecifically to scavenge H2O2. These experimental results demonstrated that each scavenging compounddifferent in its scavenge capacity toward different form of radicals.